Phytochemical analysis and ethnomedicinal uses of Oroxylum indicum in Nepal - Bhattarai, Keshab; Kunwar, Ripu; Baral, Bikash (Ethnobotany Research and Applications, 2022)
Background: Plant natural products have a long history of usage as a source of therapeutic agents. Oroxylum indicum (L.) Kurz is a prominent therapeutic plant in South Asia, comprising several phytochemicals with substantial medical significance, including the treatment of COVID-19. Methods: Herein, we documented the medicinal importance of O. indicum throughout Nepal using a questionnaire-based survey and and validated the findings through biochemical analyses. Results: All fractions (water, hexane and dichloromethane) obtained from different extraction solvents revealed a high abundance of alkaloids, flavonoids, phenolic compounds, saponins, and carbohydrates that is consistent with its vast ethnomedicinal uses generated through the questionnaire survey. Conclusions: In a nutshell, O. indicum is a promising medicinal plant based on our current experiment, and more research on ethnomedicinal and plant biochemical capabilities might lead to new scientific avenues and novel drug discoveries. It further paves the scope of documentation of traditional knowledge for the benefit of local and national communities. Keywords: antioxidant activity, COVID-19, drug discovery, Oroxylum indicum.